Should We Ban Unconventional Oil Extraction to Reduce Global Warming? - Samuel Carrara; Emanuele Massetti (Fondazione Eni Enrico Mattei (FEEM), 2014)
The extraction and processing of unconventional oil is more energy intensive and has larger negative environmental impacts than the extraction of conventional oil. The European Union (EU) estimates that oil sands lead to 22% more emissions than conventional oil. The EU is very concerned by the potential climate and environmental impacts and has considered introducing a tax on imported unconventional oil in order to discourage its production. This study shows that a global ban on the use of unconventional oil substantially reduces global carbon dioxide emissions, but the policy is not efficient. A unilateral ban of the EU on unconventional oil has no climate benefits and it is expensive for Europe.
Keywords: Q35; Q37; Q42; Q48; Q56; 330; Unconventional Oil; Climate Mitigation; Energy Policy; European Union